Indicators of sustainable development for the city and the lagoon of Venice - Emiliano Ramieri; Valentina Cogo (Fondazione Eni Enrico Mattei (FEEM), 1998)
In the past few years sustainability and sustainable development have become important concepts widespread over the world. There is no agreement on a common definition of sustainability, but there is a general need to measure and assess sustainability in different geographical and spatial contexts. Indicators of sustainable development have been defined in order to satisfy those requirements. Such indicators are very useful to improve the process towards sustainability in local systems, such as cities and towns, where they can be related to local Agenda 21 experiences. The present paper discusses the result of an investigation concerning the definition, selection and calculation of a set of indicators of sustainable development for the city and lagoon of Venice. The analysed area also includes the city of Mestre and the industrial zone of Porto Marghera. Indicators were selected by considering similar national and international experiences and the main problems linked to the sustainability of the analysed area. The present study was carried out during the same time period as the Agenda 21 implementation process in Venice. The local Agenda 21 contributed to the selection of appropriate indicators used in this study. In the selection of indicators particular attention was given to some technical criteria: measurability, simplicity, availability of data and relevance of these indicators to Venice. Chosen indicators concern the three main aspects of sustainability: quality of life, quality of the environment and quality of economic development. This paper reports the conclusion of the research and highlights the state of the sustainability of the investigated area for each indicator in relation to defined objectives or numeric targets.
Keywords: I00; J00; J11; R00; Z00; 330; Sustainability; Indicators of sustainable development; Sustainable targets; Venice; Quality of the environment; Quality of life; Quality of economic development; Urban areas; Industrial areas; Stadtentwicklung; Nachhaltige Entwicklung; Wirtschaftsindikator; Theorie; Venedig